'Nimble Fingers' in Electronic Music: Rethinking sound through neo-colonial labour. Issue 2 (12th July 2017) - Vágnerová, Lucie
Abstract : How can historians of electronic music address the factory labour of the global underclass of women building electronics used in sound technologies? How can we speak to the repetitive work of women who are racially and sexually stereotyped as having 'nimble fingers', being 'detail oriented' and 'obedient'? Although women workers in electronics assembly are already de facto entangled in contemporary sound production, scholars have yet to enfold their lives and labour into histories of electronic music. I situate electronic sound technologies since the 1960s in the contexts of the global division of labour and the intimate disciplining of women's bodies, and investigate the discursive fallout of transnational subcontracting in the electronics industry. I argue that rethinking the category 'women in electronic music' is a necessary step for sound studies and musicology, and I call for a new disciplinary understanding of electronic sound and audio as fundamentally neo-colonial.